TEKNIK PERSUASIF DALAM SPANDUK KAMPANYE CALON KEPALA DESA TAHUN 2019 DI KECAMATAN KEDAMEAN KABUPATEN GRESIK - Suwandi, Suwandi (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
This study discusses political problems from a linguistic aspect. The purpose of this study is to describe the use of persuasive techniques in the campaign banners for the 2019 village head candidates in Kedamean District, Gresik Regency. The data source used was the campaign banner for the 2019 Village Head candidate in Kedamean District, Gresik Regency. The data taken is data in the form of sentences totaling 35. The collecting data is by documenting or photographing banners in the Kedamean District, Gresik Regency. This study uses intralingual equivalent data analysis techniques using a series of corpus data. Advanced courses in analysis use note-taking methods and qualitative descriptive analysis because the data results from the documentation. The information is grouped based on the seven indicators of persuasive techniques. The research found four of the seven existing persuasive methods. The persuasive technique that is most widely used is the suggested technique of 19 sentences. The 12 sentence identification technique, the three-sentence rationalization technique, and the last one is the conformity technique with a total of 1 penalty, and no data is found that shows compensation, replacement, and projection techniques. So, the total number of data containing persuasive techniques in the campaign banners of the 2019 village head candidates in Kedamean District, Gresik Regency is 35 data, according to the number of banners studied. Keywords: Sentence, Village Head, Campaign Banner, Persuasive Technique.